2014
DOI: 10.1155/2014/385901
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Autologous Bone Marrow Stem Cell Transplantation on Matrix Metalloproteinases in Patients Treated for Acute ST-Elevation Myocardial Infarction

Abstract: Background. Matrix metalloproteinase-9 (MMP-9), regulated by tissue inhibitor of metalloproteinase-9 (TIMP-1) and the extracellular matrix metalloproteinase inducer (EMMPRIN), contributes to plaque instability. Autologous stem cells from bone marrow (mBMC) treatment are suggested to reduce myocardial damage; however, limited data exists on the influence of mBMC on MMPs. Aim. We investigated the influence of mBMC on circulating levels of MMP-9, TIMP-1, and EMMPRIN at different time points in patients included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
2
4
1
Order By: Relevance
“…All 3 markers declined significantly after the acute initial event, which is in line with previous observations [4,17]. The high circulating levels measured on day 3 were probably due to acute-phase processes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All 3 markers declined significantly after the acute initial event, which is in line with previous observations [4,17]. The high circulating levels measured on day 3 were probably due to acute-phase processes.…”
Section: Discussionsupporting
confidence: 92%
“…However, we have previously shown that expression of the EMMPRIN gene in circulating leukocytes correlated with myocardial injury, as measured by creatine kinase and SPECT-based infarct size in another group of STEMI patients [17]. As reports on EMMPRIN in this context are limited [26] and are mostly restricted to in vitro animal models, further exploration is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that in AMI patients, soluble EMMPRIN is positively correlated with infarct size, measured by single-photon emission tomography and peak CK, and inversely correlated with LVEF [34]. It can be concluded that these results, and our results demontrating that EMMPRIN is significantly positively correlated with peak CK-MB and peak cTnT, inversely correlated with LVEF, are in favour of the notion that EMMPRIN is a causative factor in AMI.…”
Section: Discussionsupporting
confidence: 76%
“…Knowledge on the temporal changes in EMMPRIN in AMI is limited, with only two published studies [14,34] on this matter. One study [14] reported that the expression level of EMMPRIN on monocytes was significantly elevated in AMI patients whose onset of chest pain was >24 hours previously, than in those whose onset of chest pain was <24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation